Adsorption and inhibition properties of Tephrosia Purpurea as corrosion inhibitor for mild steel in sulphuric acid solution. Issue 10 (3rd October 2019) - Thirumangalam Karunanithi, Bhuvaneswari; Chellappa, Jeyaprabha
Abstract: The present study investigated the adsorption and inhibition behavior of leaf extract of Tephrosia Purpurea ( T. purpurea ) on mild steel corrosion in 1 N H2 SO4 solution using electrochemical and surface morphological methods. Techniques adopted for electrochemical studies were Potentiodynamic Polarization and Electrochemical Impedance Spectroscopy (EIS) technique; and surface morphological studies were carried out using Scanning Electron Microscopy (SEM), and Atomic Force Microscopy (AFM). The leaf extract of T. purpurea was characterized using UV-Visible spectroscopy (UV-Vis), Fourier-Transform Infrared Spectroscopy (FT-IR), Nuclear Magnetic Resonance Spectroscopy (NMR) and Gas Chromatography – Mass Spectrometry (GCMS). The results obtained from electrochemical studies exhibited the potential of T. purpurea as good corrosion inhibitor. And, it was found that, the inhibition efficiency (I.E in %) increases with increase in concentration of the inhibitor molecules, the optimum inhibitor concentration observed was 300 ppm and the inhibition efficiency of 93% was observed at this inhibitor concentration. Above 300 ppm, there was not much changes in inhibition efficiency. Polarization studies provided the information that the inhibition is of mixed type and EIS confirmed that the corrosion process is controlled by single charge transfer mechanism. And, it was obtained that, the adsorption of inhibitor molecules obeys Langmuir adsorption isotherm. The inhibition is mainly by the adsorption of inhibitor molecules on the mild steel electrode surface, which was confirmed by FT-IR, SEM and AFM studies. Through all the experimental results, it can be arrived that, the leaf extract of T. purpurea performed as a good corrosion inhibitor for mild steel in 1 N sulfuric acid medium. GRAPHICAL ABSTRACT: UF0001